Evolution and expression analysis of starch synthase III and IV in rice - Dian, Weimin (Journal of experimental botany, 2005)
Plants contain at least five subfamilies of starch synthases, granule bound starch synthase (GBSS) and starch synthases I, II, III, and IV (SSI, SSII, SSIII, SSIV). In this work, two members of SSIII and SSIV, respectively, were cloned and designated OsSSIII-1/-2 and OsSSIV-1/-2 in rice. Together with six other previously reported genes, the SS gene family in rice therefore is known to be duplicated and to comprise ten SS genes distributed among the five subfamilies. The starch synthase activity of each SS was confirmed by expression and enzyme activity assay in E. coli. Expression profile analysis with reverse transcription-PCR, western blotting and zymogram, indicates that OsSSIII-2 and OsSSIV-1 are mainly expressed in endosperm, while OsSSIII-1 and OsSSIV-2 are mainly expressed in the leaves. With a similar pattern of genes encoding other enzymes for starch synthesis, (such as GBSS, SSII, ADP-glucose pyrophosphorylases, and branching enzymes), it is suggested that two divergent groups of these genes should be classified in rice. Group I genes are preferentially expressed in the endosperm and function on storage starch synthesis. Group II genes are mainly expressed in leaves and some of them in the early developing endosperm, and function on transient starch synthesis in rice